Trimethylchlorosilane-Mediated Mild α-Chlorination of 1,3-Dicarbonyl Compounds Promoted by Phenyliodonium Diacetate - Chong, Siying; Su, Yingpeng; Wu, Lili; Zhang, Weigang; Ma, Junyan; Chen, Xiaowei; Huang, Danfeng; Wang, Ke-Hu; Hu, Yulai (Synthesis, 2016)
Trimethylchlorosilane was used as chlorine source for the α-chlorination of 1,3-dicarbonyl compounds with phenyliodonium diacetate as oxidant at room temperature. The reaction allows the selective synthesis of α-monochlorinated products from different kinds of 1,3-dicarbonyl compounds in good yield. The potential possibility of this conversion for bromination has also been investigated.
Keywords: chlorination; 1,3-dicarbonyl compounds; phenyliodonium diacetate; trimethylchlorosilane; Umpolung strategy